21 Daily dynamic discharge – a whole system solution to ED crowding. Issue 12 (23rd November 2017) - Kerr, Jacques; Maitland, Helen; Bell, Claire; White, Julie; Hunter, Alan
Abstract : Introduction: ED crowding is associated with increased mortality, poor staff and patient experience, an increased inpatient length of stay and poor compliance with the four-hour emergency access standard. 1 Where crowding is caused by exit block, the focus needs to be on whole system patient management, reducing the temporal mismatch between admissions and discharges since at times of peak demand hospitals may become gridlocked until patients are discharged. In an attempt to tackle exit block, the Scottish Government Unscheduled Care Team have implemented the Daily Dynamic Discharge (DDD) approach, which aims to increase the number of inpatient discharges by 12 pm, thus enabling more timeous flow through the ED. Methods: A series of meetings were held between the Unscheduled Care Team and the clinical and managerial staff of Dumfries and Galloway Royal Infirmary over a two-week period to train staff on implementing the elements of the Daily Dynamic Discharge approach. These included holding a daily whiteboard meeting with input from the multidisciplinary team, early determination of an Estimated Date of Discharge (EDD) for each patient, and conducting 'golden hour' ward rounds whereby the highest acuity patients were seen first followed by those who were expected to be discharged that day, thus increasing the number of discharges by 12 pm. Results: Over a twelve-week period the average number of weekly discharges increased from 26.5 to 30.2, i.e., an average increase of 3.7 discharges per week. Average length of stay dropped from 6.8 days to 6.2 days, a saving of 0.6 days. The median discharge time was 32 min earlier once DDD had been implemented. Previously, a third (33%) of patients were discharged before 4 pm; after implementation, this rose to 44%. Discussion: Emergency Department activity, and particularly crowding, is the barometer for the rest of the hospital, and the only way to guarantee that patients who require admission, get into the right bed, and in a timely way, is to ensure that the downstream wards discharge sufficient numbers early in the day to accommodate admissions from the ED. The DDD approach has been shown to be effective in increasing the number of discharges by 12 pm, smoothing the admission/discharge profile, and is now being adopted in other hospitals throughout Scotland. Reference: Richardson DB. Increase in patient mortality at 10 days associated with emergency department overcrowding. Med J Aust2006;184(5):213–216.